P161 Case report of a systemic lupus erythematosus and antiphospholipid syndrome patient with an infiltrative tuberculosis and melanoma: features of therapeutic approaches. (23rd March 2020) - Shumilova, Anastasiia; Reshetnyak, Tatiana; Cheldieva, Fariza; Cherkasova, Maria; Lila, Alexander
Abstract : Background: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by multiorgan tissue damage, including skin, that is frequently treated with high doses of immunosuppressive drugs. Thus, patients with SLE are at increased risk for infections (for example, tuberculosis) and malignancy. SLE and tuberculosis may have similar presentations and mimic each other; also, prior tuberculous infection may precipitate SLE in genetically predisposed individual. An increased standardized incidence ratio for non-melanoma skin cancer has been reported, however, there is no evidence of correlation between SLE and melanoma. Methods: We report a case of a patient with SLE and antiphospholipid syndrome (APS) with a moderate disease activity index (SLEDAI = 7) with infiltrative tuberculosis and melanoma. Results: A 41-year-old female patient with SLE for 22 years, was diagnosed on the basis of skin lesion, alopecia, photosensitivity, oral ulcers, arthritis, pericarditis, hemolytic anemia, leukopenia, highly positive antibodies to dsDNA, hypocomplementemia, ANF hep-2 positivity. An anamnesis of the disease and treatment tactics are presented in table 1 . Conclusions: There are no established guidelines available for treatment of tuberculosis or melanoma in SLE patients due to lack of relevant studies and management based more on physician expertise. The use of genetically engineered biological drugs can be limited due to the high risk of infection, the onset of cancer in the anamnesis, and also not fully studied in patients with comorbidity.